Settler colonial violence in the American Southwest and German Southwest Africa - Janne Lahti (Historical Encounters: A Journal of Historical Consciousness, Historical Cultures, and History Education, 2023)
This article takes a comparative approach to settler colonial violence in the American Southwest and German Southwest Africa. The Anglo invasion of central Arizona in 1864 and the German conflict against the Herero in 1904 highlights the nature of frontier violence and identifies similarities and differences across two points in space and time that have seldom been compared by historians. Those writing of the US-Apache conflicts have failed to look to colonial theaters around the world, their transnational attention focusing instead on the borderlands of United States, Mexico, and independent Indians. Similarly, research on the violence in GSWA has not engaged systematically with international parallels and has instead focused on identifying possible links between GSWA and the Nazis and the Holocaust. This article seeks to address these shortcomings by analysing the comparative strands of settler colonial violence.